2022
DOI: 10.1088/1361-6528/ac805f
|View full text |Cite
|
Sign up to set email alerts
|

Highly sensitive fluorescent detection of EDIL3 overexpressed exosomes for the diagnosis of triple-negative breast cancer

Abstract: EDIL3 is a strong and highly accurate diagnostic marker for breast cancer, meanwhile, EDIL3 overexpressed exosomes are novel biomarkers for the early diagnosis of triple-negative breast cancer (TNBC). Here, we proposed a fluorescent detection method for EDIL3 overexpressed exosomes, which is simple and sensitive. Basically, we utilized a magnetic nanospheres (MNS) based liquid sandwich immunoassay strategy. MNS were modified with CD63 aptamers, which can immunologically bound to the CD63 protein on the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…EDIL3 was identified as a novel regulator of epithelial-mesenchymal transition (EMT), contributing to angiogenesis, metastasis, and recurrence of hepatocellular carcinoma [47]. EDIL3 is also a strong and highly accurate diagnostic marker for breast cancer [48]. Moreover, in accordance with previous studies, we found that tumor-derived EDIL3 was involved in tumor-associated bone loss [49].…”
Section: Discussionsupporting
confidence: 86%
“…EDIL3 was identified as a novel regulator of epithelial-mesenchymal transition (EMT), contributing to angiogenesis, metastasis, and recurrence of hepatocellular carcinoma [47]. EDIL3 is also a strong and highly accurate diagnostic marker for breast cancer [48]. Moreover, in accordance with previous studies, we found that tumor-derived EDIL3 was involved in tumor-associated bone loss [49].…”
Section: Discussionsupporting
confidence: 86%
“…The study found that the frequency and intensity of HLA-DR expression in the MMD-secreted EV derived from the lungs of cancer patients was higher, suggesting the enrichment of macrophages in the lungs of cancer patients [90]. In the same year, Wei et al proposed a fluorescence detection method for EDIL3-overexpressed exosomes through SMLM and proposed that EDIL3-overexpressed exosomes are novel biomarkers for the early diagnosis of triple-negative breast cancer (TNBC), which have great potential in the clinical diagnosis of TNBC [100]. The DNA-PAINT technology focused on reducing the resolution to the molecular level early.…”
Section: Single Molecule Localization Imaging Technologymentioning
confidence: 99%
“…Structurally, EDIL3 comprises two discoidin I-like repeats and three EGF-like repeats that interact with integrin to modulate endothelial cell function [ 6 , 7 ]. Recent studies have reported that EDIL3 plays critical roles in tumourigenesis, metastasis, and angiogenesis [ [8] , [9] , [10] , [11] , [12] ]. For instance, EDIL3 is overexpressed in hepatocellular carcinoma and promotes angiogenesis, invasion, and migration in vitro [ 13 ].…”
Section: Introductionmentioning
confidence: 99%